Kiev-Moscow, Part 2 - Khoreva, Elena (Ukraine, 2014)
The stories of everyday life of Kyiv and Moscow citizens of the same professions and social backgrounds. Waiters, teachers, doctors, janitors, members of parliament, actors... Ordinary heroes against the background of the ongoing dramatic events. Is there a political chasm or a hope for the peace between them? Russia and Ukraine, Moscow and Kyiv – how ordinary people cope with the realities of war in the neighboring states with a shared past and conflictual present.
Russian-Ukrainian-Estonian co-production. Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission